The Influence of Antiplatelet Drugs on Platelet Survival After Aortic Damage or Implantation of a Dacron Arterial Prosthesis - Wilkinson, A.R.; Hawker, R.J.; Hawker, L.M. (Thrombosis and Haemostasis, 1979)
The effect of antiplatelet drugs on platelet survival, as measured by indium-III labelled platelets was studied in two groups of surgically treated animals. In the dog, platelet survival and loss were measured following surgery and implantation of a dacron arterial prosthesis. These same parameters were measured after aortic damage in the rat. Animals treated with the antiplatelet drugs, sulphinpyrazone and ticlopidine were compared with controls. In the dog, the sulphinpyrazone treated animals had a significantly increased platelet survival and decreased platelet loss following surgery (p<0.05). In the rat both ticlopidine and sulphinpyrazone showed significantly increased platelet survival and decreased loss of platelets following surgery when compared with controls (p< 0.001).We conclude that both ticlopidine and sulphinpyrazone merit evaluation as potential agents for reducing the risk of thrombotic occlusion in peripheral vascular disease and also in patients with arterial prostheses.